OUTFLOW OF THE BIOGENIC SUBSTANCES IN THE DRAINAGE AREA OF SŁAWSKIE LAKE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The intent of the author is to familiarize the readers with the results of the research on the anthropogenic eutrophication of the Sławskie Lake where it is impossible or difficult to apply technical measures preventing the pollution. It is a shallow, eutrophic lake where, the structure and functioning – especially the accessibility of easily assimilated biogenic compounds, especially the phosphorus – depends significantly of the fate and speed of decay of the organic matter brought to that ecosystem from the drainage area. For the last several years observed was (in that researched lake) strong blossoming of algae and cyanosis constituting the proof of its periodically sudden eutrophication. A proper description of the volume of the area pollution and determination of the outflow indicators for the water transferring lakes is difficult because the volume of the outflow of the wastes is influenced not only by their diversified contents – being the result of the combination of individual components in varying proportions – but also their influence as a result of certain local conditions. Thus, the results obtained by different authors show big differences and even discrepancies. On the basis of the conducted research it was determined that the most adequate relation (with a similar character of the area) is for the researched drainage area the one between the load of the biogenes and the volume of the indicators of their unit outflow.